The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s00253-016-8059-6
|View full text |Cite
|
Sign up to set email alerts
|

Simulated microgravity affects some biological characteristics of Lactobacillus acidophilus

Abstract: The effects of weightlessness on enteric microorganisms have been extensively studied, but have mainly been focused on pathogens. As a major component of the microbiome of the human intestinal tract, probiotics are important to keep the host healthy. Accordingly, understanding their changes under weightlessness conditions has substantial value. This study was carried out to investigate the characteristics of Lactobacillus acidophilus, a typical probiotic for humans, under simulated microgravity (SMG) condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 34 publications
1
29
0
Order By: Relevance
“…For instance, proteins related to the amino acid decarboxylase were detected upregulated in lactic acid bacteria at low pH . Other research also found simulated microgravity could markedly shorten the lag phase of Lactobacillus acidophilus , enhanced its growth rate, acid tolerance ability, and a mannose‐specific adherence mechanism in Lactobacillus plantarum conferring binding to the human colonic cell line HT‐29 . All these findings provided valuable information for understanding the influence of probiotics on human health.…”
Section: Introductionmentioning
confidence: 80%
“…For instance, proteins related to the amino acid decarboxylase were detected upregulated in lactic acid bacteria at low pH . Other research also found simulated microgravity could markedly shorten the lag phase of Lactobacillus acidophilus , enhanced its growth rate, acid tolerance ability, and a mannose‐specific adherence mechanism in Lactobacillus plantarum conferring binding to the human colonic cell line HT‐29 . All these findings provided valuable information for understanding the influence of probiotics on human health.…”
Section: Introductionmentioning
confidence: 80%
“…Some of these studies detected compositional changes in culturable bacteria collected from the GIT of astronauts spending up to 2 months in space ( 91 , 92 ). The identified changes included a post-flight reduction of lactobacilli, some of which are beneficial to human health ( 93 , 94 ) and increased levels of enterobacteria and clostridia. Another study identified a significant pre-flight reduction in bifidobacteria that was attributed to the stressful conditions, cosmonauts are exposed to during their preparation for the incoming flight ( 95 ).…”
Section: Microbiome and Probioticsmentioning
confidence: 99%
“…In short-and long-term space travel or space simulators, crew members are exposed to harsh space environments and experience changes in dietary models that can potentially affect the composition and function of their gut microbiomes, which may have a negative effect on their health. Previous studies performed on simulated or real outer-space conditions have suggested that space travel may cause both compositional (2,32,33) and functional (34)(35)(36)(37) changes in the gut microbiome. However, it is not clear what happens to the human gut microbiome when humans are in a simulated outer-space environment with specialized diets and closed sources of vital necessities such as water and oxygen.…”
Section: Discussionmentioning
confidence: 99%